Development of a knowledge-based manufacturing modelling system based on IDEF0 for the discrete manufacturing industry - Luo, Ming. (2011)
This research looks into a new area for knowledge-based system application, that of manufacturing modelling using IDEFO. though a powerful tool for the modelling of manufacturing systems, IDEFO is not without weakness. First, the IDEFO modelling process can be time-consuming. this is so even with the aid of a commerically-available software package, and especially when the system modelled is large and complex. Second, the process can also be inconsistent. The problem occurs because the interfaces in IDEFO are not precisely define and hence are subject to individual interpretations. however, the process can be automated to improve time-effectiveness and inconsistency. Most, if not all, of the commercially available software packages for IDEFO modelling are nothing more than a computer-aided drafting system. Then have very little or no intelligence. this research proposes a knowledge-based system for automating the process. The system is basically a computer program which includes the various kninds of human knowledge that are required to build IDEFO models of manufacturing systems based on the concept of reference models. It is meant for the discrete manufacturing industry and is intended for the modellers of manufacturing systems as an aid in just the same fashion as variant computer-aided process planning systems are intended for the process planners.